2014
DOI: 10.1074/jbc.m113.500868
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding by Sgf11 Protein Affects Histone H2B Deubiquitination by Spt-Ada-Gcn5-Acetyltransferase (SAGA)

Abstract: Background:Histone deubiquitination by SAGA is a core mechanism in gene expression regulation. Results:The zinc finger domain of SAGA subunit Sgf11 interacts with nucleosomal DNA via a positively charged surface patch. Conclusion: This interaction is required for optimal deubiquitination activity. Significance: This work highlights the unexpected role of C2H2-like zinc fingers in SAGA complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Sgf11 is a Znf protein and can bind to nucleosomal DNA (Koehler et al 2014). Moreover, we found that Znf-binding sites are enriched in the Sgf11-specific targets (Supplemental Table S6).…”
Section: Dub and Hat Module Subunits Control Expression Of A Subset Omentioning
confidence: 75%
“…Sgf11 is a Znf protein and can bind to nucleosomal DNA (Koehler et al 2014). Moreover, we found that Znf-binding sites are enriched in the Sgf11-specific targets (Supplemental Table S6).…”
Section: Dub and Hat Module Subunits Control Expression Of A Subset Omentioning
confidence: 75%
“…A previous report by another group demonstrated that the ZnF-Sgf11 domain of ATXN7L3 is essential for DUB activity toward H2Bub1 in vitro (6). The ZnFSgf11 domain is also required for ATXN7L3 binding to nucleosomal DNA (11), and the crystal structure of the DUB module reveals that an arginine cluster in the ZnF-Sgf11 domain directly interacts with ubiquitinated nucleosomes and H2A/H2B heterodimer (12). Therefore, the absence of this domain in ATXN7L3B indicates that it is unlikely to interact with histones, consistent with our findings that the ATXN7L3B-DUB module cannot efficiently deubiquitinate histones in vitro and that ATXN7L3B is largely localized to the cytoplasm in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The ZnF-Sgf11 domain of ATXN7L3 is essential for DUB activity toward H2Bub1 in vitro (6). The ZnF-Sgf11 domain is required for ATXN7L3 binding to nucleosomal DNA (11), and the crystal structure of the DUB module reveals that an arginine cluster in the ZnF-Sgf11 domain directly interacts with ubiquitinated nucleosomes and H2A/H2B heterodimer (12).…”
mentioning
confidence: 99%
“…Ubp8 is inactive until interacting with the other DUB module subunits, indicating that all four components are required for optimal enzymatic activity (Kö hler et al, 2008). The Sgf73 and Sgf11 subunits harbor the conserved SCA7 and Zinc finger domains, respectively, which have been shown to interact with nucleosomes (Bonnet et al, 2010;Koehler et al, 2014). The incorporation of a long polyglutamine expansion into ATXN7, the human homolog of Sgf73, leads to type 7 spinocerebellar ataxia (David et al, 1997;Helmlinger et al, 2004).…”
Section: Introductionmentioning
confidence: 97%